{2y4−y2√4x+3−3=4x............................(1)(27x3+63x2+43x+7)(y2+1)=16x2+24x+8.......(2)Điều kiện: x≥−34.
(1)⇔(y2−√4x+3)(2y2+√4x+3)=0
\Leftrightarrow \left[ \begin{array}{l} y^2=\sqrt{4x+3}\\ 2y^2+\sqrt{4x+3}=0\Rightarrow y=2;x=-\frac{3}{4} (loại) \end{array} \right.
Thay y^2=\sqrt{4x+3} vào PT (2), ta được:
(27x^{3}+63x^{2}+43x+7)(\sqrt{4x+3}+1)=16x^{2}+24x+8
\Leftrightarrow (x+1)(27x^{2}+36x+7)(\sqrt{4x+3}+1)=8(x+1)(2x+1) (vì x+1>0,\forall x \ge -\frac{3}{4}. )
\Leftrightarrow (27x^{2}+36x+7)(4x+2)=8(2x+1)(\sqrt{4x+3}-1) (vì x=-\frac{1}{2} không phải nghiệm của hệ)
\Leftrightarrow 27x^2+36x+7=4(\sqrt{4x+3}-1)
\Leftrightarrow 27x^2+36x+11=4\sqrt{4x+3}
\Leftrightarrow (27x^2+36x+11)^2=16(4x+3) (x \ge \frac{-6+\sqrt{3}}{9})
\Leftrightarrow 729x^4+1944x^3+1890x^2+728x+73=0
\Leftrightarrow (9x^2+8x+1)(81x^2+144x+73)=0
\Leftrightarrow x=\frac{-4+\sqrt 7}{9}\Rightarrow y= \pm \frac{2+\sqrt7}{3}
Kết luận: hệ đã cho có nghiệm là: \color{red}{(x;y)=(\frac{-4+\sqrt 7}{9}; \pm \frac{2+\sqrt7}{3})}.